Exercice sur l’analyse de réseaux : l’exemple de la vénalité des offices dans l’Empire espagnol (1704-1711) - Émilie Senmartin (Les Cahiers de Framespa)
Graphs are often perceived by historians as simple representations or illustrations of existing networks and are consequently hardly studied per se. This paper will not consider graphs as simple objects answering the precise needs of scholars at one point in time. Instead, it will deconstruct the historical inquiries made by researchers in order to show that graphs can become a real object of study. By focusing on Francisco Andújar Castillo's diagrams and graphs (Necesidad y Venalidad. España e Indias. 1704-1711), this paper will examine the merits and utility of graphs in general.